2012
DOI: 10.1590/s0006-87052012000100007
|View full text |Cite
|
Sign up to set email alerts
|

Espaçamentos entre plantas e cobertura do solo com cama-de-frango na produção de ervilhas

Abstract: ResumoO presente trabalho teve por objetivo avaliar a produção agroeconômica da ervilha Luciana n.º 50, cultivada sob três espaçamentos entre plantas (5,0; 7,5 e 10,0 cm), com e sem cobertura do solo com cama-de-frango. Os tratamentos foram arranjados como fatorial 3x2, no delineamento experimental de blocos casualizados, com cinco repetições. As maiores massas frescas (8,33 t ha -1 ) e secas (2,02 t ha -1 ) da parte aérea foram das plantas cultivadas sob espaçamento de 7,5 cm e as menores (7,87 t ha -1 e 1,82… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2016
2016
2016
2016

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 4 publications
0
1
0
Order By: Relevance
“…Achakzai (2012), while evaluating pea cultivars, found plant height variation between 53.65 to 57.79 cm. Zárate et al (2012), while evaluating pea crop spacings, observed that there was no significant effect for number of pods per plant and pod length. - ns , * -not significant and significant at 1% probability, respectively, by F test; means followed by the same letter in the column do not differ by Tukey's test at 5% probability.…”
Section: Resultsmentioning
confidence: 95%
“…Achakzai (2012), while evaluating pea cultivars, found plant height variation between 53.65 to 57.79 cm. Zárate et al (2012), while evaluating pea crop spacings, observed that there was no significant effect for number of pods per plant and pod length. - ns , * -not significant and significant at 1% probability, respectively, by F test; means followed by the same letter in the column do not differ by Tukey's test at 5% probability.…”
Section: Resultsmentioning
confidence: 95%